Chiral Separation: Mechanism Modeling in Two-Dimensional Systems. - Paci, Irma; Szleifer, Igal; Ratner, Mark A. (Journal of the American Chemical Society, 2007)
Fluid phase separations of racemates are difficult because the subtle, short-ranged differences in intermolecular interactions of like and unlike pairs of chiral molecules are typically smaller than the thermal energy. A surface restricts the configurational space available to the pair of interacting molecules, thus changing the effective interactions between them. Because of this restriction, a surface can promote chiral separation of mixtures that are racemic in bulk. In this paper, we investigate chiral symmetry breaking induced by an achiral surface in a racemate. A parallel tempering Monte Carlo algorithm with tempering over the temperature domain is used to examine the interplay between molecular geometry and energetics in promoting chiral separations. The system is restricted to evolve in two dimensions. By controlling the balance between electrostatic and steric interactions, one can direct the surface assembly of the chiral molecules toward formation of small clusters of identical molecules. When molecular shape asymmetry is complemented by dipolar alignment, chiral micellar clusters of like molecules are assembled on the surface. We examine the case of small model molecules for which the two-dimensional restriction of the pair potential is sufficient to induce chiral segregation. An increase in molecular complexity can change the balance of intermolecular interactions to the point that heterochiral pairs are energetically more favored. In this case, we find conditions in which formation of homochiral micelles is still achieved, due to a combination of multibody and entropic effects. In such systems, an examination of the pair potential alone is insufficient to predict whether the multimolecular racemate will or will not segregate.